Handbook of milk composition - Jensen, Robert G. (Food science and technology international series., 1995)
This informative treatise offers a concise collection of existing, expert data summarizing the composition of milk. The Handbook of Milk Composition summarizes current information on all aspects of human and bovine milk, including: sampling, storage, composition, as well as specific chapters on major and minor components such as protein, carbohydrates, lipids, electrolytes, minerals, vitamins and hormones. The book also features comprehensive coverage of compartmentation, host-defense components, factors affecting composition, composition of commercial formulas, and contaminants.